STUDI NILAI TAMBAH RUMPUT LAUT (Kappaphycus sp) MENJADI ALKALI TREATED COTTONII (ATC) - Ferdinan, Ferdinan; Sunadji, Sunadji; Ratoe Oedjoe, Marcelien Dj (Jurnal Aquatik, 2025)
This study aims to analyze the added value resulting from processing Kappaphycus sp seaweed into Alkaline Treated Cottonii (ATC) and to evaluate the economic aspects of the process. The ATC processing process is carried out through boiling seaweed with a solution of potassium hydroxide (KOH) at a temperature of 80–85°C for two hours, followed by washing, cutting, and drying. The results of the study showed that the processing of dried seaweed into ATC produced an added value of Rp 67,000 per kilogram of dried seaweed, with a total added value for 100 kg of seaweed reaching Rp 7,210,000. This added value reflects a significant increase in the selling price of processed products compared to the sale of seaweed in raw form. Financial analysis showed a gross profit of IDR 5,900,000, with a break-even point reached in the production of around 28.45 kg of ATC. This study concludes that processing seaweed into ATC not only increases the economic value of the product, but also opens up opportunities for product diversification such as pure carrageenan which is in great demand in the international market. Therefore, processing seaweed into ATC can provide great economic benefits for coastal communities and can improve the welfare of business actors through the added value produced. Keywords: Alkali Treated Cottonii (ATC), economics, Kappaphycus sp, carrageenan, added value, processing